2011
DOI: 10.1007/s00222-011-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Gromov-Witten/Donaldson-Thomas correspondence for toric 3-folds

Abstract: We prove the equivariant Gromov-Witten theory of a nonsingular toric 3-fold X with primary insertions is equivalent to the equivariant Donaldson-Thomas theory of X. As a corollary, the topological vertex calculations by Agangic, Klemm, Mariño, and Vafa of the GromovWitten theory of local Calabi-Yau toric 3-folds are proven to be correct in the full 3-leg setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
245
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(253 citation statements)
references
References 39 publications
6
245
0
2
Order By: Relevance
“…In [21,22] Lagrangian Floer theory is employed to study the case when the boundary condition is a fiber of the moment map. In the toric context, a mathematical approach [13,33,54,68] to construct operatively a virtual counting theory of open maps is via the use of localization [3,4,8,41,59], quantum knot invariants [47,62], and ordinary Gromov-Witten and DonaldsonThomas theory via "gluing along the boundary" [2,60,63]. Since Ruan's influential conjecture [69], an intensely studied problem in Gromov-Witten theory has been to determine the relation between GW invariants of target spaces related by a crepant birational transformation (CRC).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In [21,22] Lagrangian Floer theory is employed to study the case when the boundary condition is a fiber of the moment map. In the toric context, a mathematical approach [13,33,54,68] to construct operatively a virtual counting theory of open maps is via the use of localization [3,4,8,41,59], quantum knot invariants [47,62], and ordinary Gromov-Witten and DonaldsonThomas theory via "gluing along the boundary" [2,60,63]. Since Ruan's influential conjecture [69], an intensely studied problem in Gromov-Witten theory has been to determine the relation between GW invariants of target spaces related by a crepant birational transformation (CRC).…”
Section: 2mentioning
confidence: 99%
“…Restricting to the coordinate hyperplanes of the fundamental class insertions, the existence of the non-equivariant limits of U X ,Y ρ and the J-functions is guaranteed by the fact that we employ a torus action acting trivially on the canonical bundle of X and Y ; see e.g. [63].…”
Section: 12mentioning
confidence: 99%
“…In [17], it was shown that, for a toric CY, Z BPS is equal to Z top up to a factor which depends only on q. Here we derived the relation between Z BPS and Z top including the factor of M (q) χ/2 .…”
mentioning
confidence: 91%
“…The relation between the GV invariants and DT invariants was suggested and formulated in [13,16], and its physical explanation was given in [4] using the 4D/5D connection [8]. More recently, a mathematical proof of the GV/DT correspondence was given in [17] when X is a toric CY 3-fold.…”
mentioning
confidence: 99%
“…In the forthcoming paper [44], the most general local Calabi-Yau toric geometry involving the 3-leg vertex is analysed for the Gromov-Witten/Donaldson-Thomas correspondence. It is likely the same path of argument will apply to stable pairs theory also.…”
Section: 3mentioning
confidence: 99%